Big Data Applications and Services 2017 The 4th International Conference on Big Data Applications and Services - Lee, Wookey; Leung, Carson K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This proceedings volume contains selected papers from the Fourth International Conference on Big Data Applications and Services (BigDAS 2017), held in Tashkent, Uzbekistan on August 15-18, 2017. Big data has become a core technology providing innovative solutions in many fields including social media, healthcare and manufacturing. The Fourth International Conference on Big Data Applications and Services (BigDAS 2017) presented innovative results, encouraged academic and industrial interaction, and promoted collaborative research in the field of big data worldwide. The conference was organized by the Korea Big Data Services Society and National University of Uzbekistan.
Chapter 1. 3D volume visualization system based on GPUs for medical big data -- Chapter 2. A fire frame simulation scheme with massively parallel processing -- Chapter 3. A framework for calculating damages of personal information leakage accidents -- Chapter 4. A hierarchical structure for representing 3D respiration organ models -- Chapter 5. An effective method for detecting outlying regions in a 2-dimensional array -- Chapter 6. An effective recall-oriented information retrieval system evaluation -- Chapter 7. Chentry: Automated Evaluation of Students' Learning Progress for Entry Education Software -- Chapter 8. Constrained big data mining in an edge computing environment -- Chapter 9. Constrained frequent pattern mining from big data via crowdsourcing -- Chapter 10. Data-driven prediction of ship destinations in the harbor area using deep learning -- Chapter 11. Design and implementation of a sunshine duration calculation system with massively parallel processing -- Chapter 12. Developing3D annotation features for 3D digital textbooks -- Chapter 13. Efficient mining of time interval-based association rules -- Chapter 14. Investigating the role of musical genre in human perception of music stretching resistance -- Chapter 15. Keyword-based metadata modeling for experimental omics data dissemination -- Chapter 16. Non-linear time-series mining of social influence -- Chapter 17. PEGASEF: A provenance-based big data service framework for efficient simulation execution on shared computing clusters -- Chapter 18. Preference-aware music recommendation using song lyrics -- Chapter 19. Real time smart safe-return-home service based on big data analytics -- Index.
Keywords: Computational intelligence; Big data; Telecommunication; Multimedia systems; Social media; Computational Intelligence; Big Data; Communications Engineering, Networks; Multimedia Information Systems; Social Media